Новые данные к палеотериологической характеристике тираспольского (миндельского) яруса в составе хаджибейской свиты - Топачевский, В.А.; Корниец, Н.Л.; Свистун, В.И. (Вестник зоологии, 1975)
A detailed description is given for a new occurrence of remains of the Early Anthropogen terrestrial vertebrates and fresh-water fish. This occurence was detected in the ledge of the Khadjibei liman left bank near the vil. of Morozovka (the Odessa Re- gion). Besides Insectivora, Lagomorpha and Rodentia, there were found here Mammuthus trogontherii Pohl. and Equus mosbachensis Reih. By its species composition the Morozovkian theriofauna is probably one of the latest variants of the Tiraspol faunistic complex. Proceeding from this fact, the bench of sands of alluvial nature ought to be referred to the upper series of the Tiraspol (Mindel) stage. Determining the position of this stage in the general complex of ancient alluvial deposits of the Khadjibei suite it was established that the terraces of this geological age are characterized here by a considerable downcutting into Maeotis as compared with those of the Khaprovian (Villafrankskian) and Taman (Günz) time.